DEVELOPMENT OF CONTEXTUAL ELECTRONIC LEARNER WORKSHEET FOR PRACTICAL MATHEMATICS (E-LKPD) BASED ON LIVEWORKSHEETS TO IMPROVE THE MOTIVATION OF GRADE X STUDENTS TO LEARN MATHEMATICS - Azzahro', Qissiisiina; Handayani, Ucik Fitri (Jurnal Pendidikan Matematika dan IPA, 2025)
The implementation of mathematics learning in class X of SMK As-Salam revealed that students have difficulty in understanding mathematical concepts because learning methods are predominantly conventional and lack the connection of material to real life. Therefore, an e-LKPD based on live worksheets with contextual problems was developed. This study focuses on testing the validity, practicality, and effectiveness of the e-LKPD based on Liveworksheets. This study aims to develop a contextual e-LKPD based on live worksheets to increase the learning motivation of mathematics students in class X at SMK As-Salam. The research method used is the ADDIE (Analysis, Design, Development, Implementation, Evaluation) development model. The developed e-LKPD was validated by experts and tested for practicality through teacher and student responses. The validation results showed that the e-LKPD fell into the highly valid category with a score of 3.668. The product's effectiveness was tested using a paired sample t-test. Based on the analysis of data from 31 students, the average learning motivation score was 51% before treatment and 66% after treatment. The calculated t-value was -3.655, indicating that the e-LKPD is effective, and the sig. (2-tailed) value was 0.000, which is less than 0.05. Therefore, there was a significant increase in student learning motivation after using the e-LKPD. The conclusion of this study shows that contextualized e-LKPD based on live worksheets is effective in increasing students' motivation to learn exponent material. Therefore, it is expected that this e-LKPD can be used as an alternative to innovative learning media to improve the quality of mathematics learning.